Influencer Academy: Implementasi Pengembangan Strategi Komunikasi Relawan Penyintas Bencana - Sulaeman, Pradika; Nasution, Sri Mulyani; Andriani, Astri Dwi; Agustinah, Aminah; Rahmat S, Asep Deden; Muttaqin, Engkin Zainal (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
In higher education, where it is required to create superior human resources, digitalization is a challenge that must be overcome both administratively and in, terms of learning functions. The occurrence of the COVID-19 pandemic seems to encourage and force the implementation of digital education, one of the implementations of which is an online learning system. The online learning system should not be an obstacle that discourages the pursuit of knowledge. The academic community of Universitas Putra Indonesia (UNPI) Cianjur in collaboration with the Faculty of Psychology, Jayabaya University is trying to answer all the challenges above in the form of Community Service activities with the Short Class – Influencer Academy program. Through the Short Class – Influencer Academy program. This activity uses the Service-Learning or SL method, which is an activity that involves practical experience, academic learning, and community involvement. Activities will take place from 20 December 2022 to 20 January 2023. From the activities that have been carried out, it is concluded that this activity can not only be carried out for disaster survivors but can become an annual program to prepare advanced students to enter higher education.